Representasi Image Anak Muda Dalam Budaya Ngopi - Dhaehasti Agustina Saputri; Novia Budi Lestari; Rolika Firinanda (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Coffee culture among young people is often an activity that is seen as commonplace in modern society. Get together with friends while discussing simple and relaxed topics. Even at this time, cafes and angkringan are places to stop for young people when doing activities outside the home. Balanced with the growing sophistication of technology as a medium for distributing information as well as breaking into the space for innovation in global competition. Developments in technology and social media make it easier for young people to communicate, exchange ideas, and access the latest trending information. This condition then supports the coffee culture to be increasingly recognized by the public at large because of technological developments that have given rise to various social media, people are able to efficiently obtain information regardless of distance and time. This has an impact on young people so that it creates a consumptive mindset and behavior and forms a new lifestyle. In this research, researchers used qualitative methods with an ethnographic approach to analyze the image of young people formed as a result of a shift in coffee culture. The results of this study indicate that the image of young people who drink coffee today is constructed by the views of society. However, this view cannot be used as a reference in shaping individual social status.